An investigation into patterns of interaction in small teaching groups at Rhodes University, with particular emphasis on the effect of gender, mother-tongue and educational background - Hunt, Sally Ann (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1997)
The assumption underlying this study is that knowledge is constructed through interaction. Small teaching groups, or tutorials, are often regarded as a particularly effective context for learning in the setting of tertiary education in that they provide an environment for free interaction between students, and thus facilitate active learning. Factors which systematically affect the degree of participation of the individual in tutorIals -directly affect the learning experience of that individual and raise questions about the equality achieved in tutorials, in terms of opportunities for learning. This study focuses on one such type of factor: culturally acquired norms of interaction. The individual is seen as a composite of cultural identities, utilising norms acquired through socialisation and experience in appropriate contexts. Previous research has demonstrated that gendered norms of interaction and those associated with the individual's mother-tongue are particularly salient. In the educational context, norms acquired through previous experience of education are likely to be carried over to the new setting of the university. Thus these factors form the focus of this study. One flrst-year tutorial from each of five departments in the Faculties of Arts and Social Science at Rhodes University, Grahamstown, was video-recorded and the data thus obtained was analyzed for patterns of interaction in terms of gender, mother-tongue and educational background. A model of utterance types was developed to provide a structured description of the patterns found in the tutorials. Interviews and video-sessions with a sample of the tutorial members were conducted, which add a qualitative dimension to the investigation and allow for triangulation. The recorded tutorials and interviews reveal a marked awareness amongst students of the composition of tutorial groups in terms of gender and ethnicity and this composition appears to affect the relative participation of students, in that members of numerically dominant groups are more willing to participate. This is particularly clear in the case of female students. With regard to second-language (L2) speakers of English, a number of factors are highlighted which tend to decrease participation. Apart from problems with English as the medium of instruction, these students tend to be reluctant to participate due to cultural norms, according to which students, as subordinates, should not take the initiative in interaction, in order to show appropriate respect. Patterns of interaction by L2 students from racially integrated schools, however, do not conform to this set of norms as strongly. It is argued that sensitivity is required to address this situation and a number of options are presented.
Keywords: Tutors and tutoring; Multicultural education-- -- South Africa; Group work in education; Small groups-- Study and teaching (Higher)